Upaya Guru Bimbingan Konseling Terhadap Dampak Pembelajaran Sistem Online Masa Pandemi Covid-19 pada Siswa SMA Negeri 2 Amarasi Barat: Indonesia - Taebenu, Yulinda; Ingunau, Temy; Leto, Oktovianus (Universitas Persatuan Guru 1945 NTT, 2023)
West Amarasi 2 Public High School implemented online system learning media during the Covid-19 pandemic since the outbreak of the covid-19 occurred for 4 semesters, until it ended until now, of course students who experienced changes in learning patterns had positive and negative impacts on students the. The positive impact carried out by students and teachers in online learning is that teachers and students are able to learn and master technology, the material shared by students who do not know the teacher is more creative in the methods used during the online learning process. In the online process there are negative impacts, namely the process of learning material is incomplete, limitations in the use of technology (mobile phones, computers, networks, internet pulses) which are difficult to access, there is a buildup of assignments from subject teachers, lack of communication when there are difficulties in doing assignments. The method that will be used in this research is descriptive qualitative. This research is used to develop a theory that is built from data obtained in the field through observation. Research Results of Online System Learning During the Covid-19 Pandemic in Amarasi Barat 2 Public High School Students learn through distance by using the zoom application, google class room, whatsapp group and Facebook group. Efforts of Teacher Counseling Guidance In online system learning there is no face-to-face face-to-face between the teacher and students but it is done online using a network on the internet. The teacher must prove that teaching and learning activities continue as usual. The solution that must be done is to be able to process learning media as innovative, creative and able to think critically to utilize online media (online).